TUPLE MODEL FOR FORMING THE DATABASE OF INITIAL PARAMETERS FOR ASSESSING THE STATE SECRET PROTECTION STATUS - Korchenko, Oleksandr; Dreis, Yurii (Ukrainian Scientific Journal of Information Security, 2022)
Protection of information with limited access, especially state secrets, is an important task in the sphere of national and information security of the state. In order to minimize possible harm to Ukraine’s national security from violations in the sphere of state secrets protection and to reduce the negative international rating and other serious consequences at the state level, the task of creating specialized databases, development and improvement of existing methods and models that implement appropriate assessments is urgent. That is why the theoretical and multiple presentation of the parameters of the generalized report and the Report on the state of security of state secrets in the root models allow to solve the actual scientific and practical problem of formalization of the process of assessment of negative consequences of the leak of state secrets, its disclosure or loss of material carriers of secret information, violation of the regime of secrecy, etc. Developed root model of primary parameters and its hierarchical structure due to the integrated theoretical and multiple representation of sets characterizing the subject of secret-regime activity, specificity, nature and type of violation, expenses on measures of state secret protection, information about the secret-regime body, compliance with the regime of secrecy and normative recommendations allows to define sets of input and output parameters for formation of special databases and formalization of the process of assessment of the damage to national security from the outflow of state secrets in accordance with the requirements of the current legislation. Further, to implement the above process, it is necessary to develop appropriate models for internal and secondary parameters.